2013
DOI: 10.1097/wnp.0b013e3182873254
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of Quantitative Sudomotor Axon Reflex Testing

Abstract: We observed moderate test-retest reliability for QSART with a large standard error of measurements and minimal detectable changes for both men and women. The results of this study suggest limited utility of QSART for monitoring sudomotor function in longitudinal and interventional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…35 One recent study demonstrated that test-retest reliability can be moderate with a large standard error of measurement. 36 The results further suggested a limited utility of QSART for longitudinal and interventional studies. It is unclear where QSART stands in the diagnosis of SFN, but, similar to QST, it should not be used as the only investigation modality to confirm SFN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 One recent study demonstrated that test-retest reliability can be moderate with a large standard error of measurement. 36 The results further suggested a limited utility of QSART for longitudinal and interventional studies. It is unclear where QSART stands in the diagnosis of SFN, but, similar to QST, it should not be used as the only investigation modality to confirm SFN.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with SFN the assessments of somatic (skin biopsy and QST) and peripheral autonomic small fiber function (QSART) are complementary and, when combined, improve the sensitivity for diagnosis of SFN . One recent study demonstrated that test–retest reliability can be moderate with a large standard error of measurement . The results further suggested a limited utility of QSART for longitudinal and interventional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, other autonomic testing methodologies should be explored for sexual dysfunction characterization in MS patients. Other autonomic tests, such as acetylcholine skin tests (Berger and Kimpinski, 2013;Kandeel et al, 2001), still hold the promise for diagnosing various types of autonomic neuropathy that contributes to erectile dysfunction in MS.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative sudomotor axon reflex test is an alternative diagnostic tool but test and pretest reliability have been found to be moderate. 4 Finally, microneurography is an invasive test, which by placing recording microelectrodes within nerve fascicles, enables multiple small fibers to be recorded simultaneously. 5 The diagnosis of the underlying cause of subacute monophasic small fiber neuropathy depends on the identification of likely underlying causes.…”
Section: Sectionmentioning
confidence: 99%